Pembelajaran Pendidikan Agama Islam Untuk Anak Berkebutuhan Khusus - Faihanah, Laili; Muniroh, Alimul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aimed to describe the teaching and learning of Islamic Education for children with special needs in the school (SLB). Conducted at SLB Dharma Wanita, Ujung Pangkah Gresik, design of the research used a case study. Data collection used participant observation, interview and documentation. The results of the study showed that Islamic learning and education for children with special needs at SLB Dharma Wanita was carried out not only emphasizing in the cognitive aspects, but also in effective and psychomotor aspects. Teachers prepared lesson material, determined media, method and evaluation of teaching. The factors, which supported the learning of Islamic Religious Education for students with special needs included presence of teacher, pleasant of school building, and completeness of facilities of school. The obstacle factors in learning for student with special needs are the classroom condition, the level of intelligence and sensitivity of children, student tardiness at school and parental factors. For solution of obstacle factors, school could implement teaching and learning in the open area, provide an access to pick-up facilities and provide the control books of parent and teacher as well as provide special teachers to the students.